Correlation between altered gut microbiota and elevated inflammation markers in patients with Crohn’s disease - Hu, Jun; Cheng, Sijing; Yao, Jiayin; Lin, Xutao; Li, Yichen; Wang, Wenxia; Weng, Jingrong; Zou, Yifeng; Zhu, Lixin; Zhi, Min (Frontiers in Immunology, 2022)
Prior studies reported inconsistent results on the altered gut microbial composition in patients with Crohn’s disease (CD), likely under the influences of many confounding factors including genetic, life style and environmental variations among different study cohorts. This study aims to examine the gut microbiota of CD patients with particular efforts to minimize the impact of the confounding factors. For this purpose, the healthy relatives of the patients were enrolled as control subjects so that the paired study subjects may have similar genetic background, dietary habits, and household environment. The fecal microbiota of the study subjects were examined by 16S rRNA sequencing. After the identification of the differential bacterial genera, multivariate regression analysis was performed to adjust the results for the impact of confounding factors. We found that the microbiota of the CD patients were featured with reduced short chain fatty acid (SCFA) producing bacteria and elevated opportunistic pathogen Escherichia-Shigella. Correlation analysis indicated that the elevation in Escherichia-Shigella and the reduction in SCFA-producing bacteria usually occur simultaneously. These differential genera exhibited a high capacity in distinguishing between CD and healthy controls achieving an area under curve of 0.89, and were correlated with the changes in inflammation related blood biochemical markers. Consistent with the reduction in SCFA-producing bacteria in CD, metabolomics analysis revealed decreased blood level of SCFAs in the patients. The differential genera identified in this study demonstrated outstanding capability to serve as diagnosis markers for CD and are potential targets for intervention.